Curves and surfaces for CAGD : a practical guide. - Farin, Gerald E., 1953- (San Francisco : Morgan Kaufmann, 2002)
Chapter 1 P. Bézier: How a Simple System Was Born Chapter 2 Introductory Material Chapter 3 Linear Interpolation Chapter 4 The de Casteljau Algorithm Chapter 5 The Bernstein Form of a Bézier Curve Chapter 6 Bézier Curve Topics Chapter 7 Polynomial Curve Constructions Chapter 8 B-Spline Curves Chapter 9 Constructing Spline Curves Chapter 10 W. Boehm: Differential Geometry I Chapter 11 Geometric Continuity Chapter 12 Conic Sections Chapter 13 Rational Bézier and B-Spline Curves Chapter 14 Tensor Product Patches Chapter 15 Constructing Polynomial Patches Chapter 16 Composite Surfaces Chapter 17 Bézier Triangles Chapter 18 Practical Aspects of Bézier Triangles Chapter 19 W. Boehm: Differential Geometry II Chapter 20 Geometric Continuity for Surfaces Chapter 21 Surfaces with Arbitrary Topology Chapter 22 Coons Patches Chapter 23 Shape Chapter 24 Evaluation of Some Methods Appendix A Quick Reference of Curve and Surface Terms Appendix B List of Programs Appendix C Notation References Index
Keywords: Computer graphics